Threads of globalization fashion, textiles, and gender in Asia in the long twentieth century - Belli Bose, Melia ca. 20./21.Jh (Studies in design and material culture, 2024)
"This richly illustrated, interdisciplinary volume situates fashion, including specific garments, motifs, materials, and methods of production, at the nexus of modernity, tradition, and identity, bringing these factors into Pan-Asian dialogure. exploring the impact of textiles and garments on bothe national and local cultural identity, as well as gender identity and personal expression. Threads of globalization also investigates how garment and textile production has influenced women's creative agency. The final section of the book examines examples of artivism that critique the often-gendered structural violence and environmental impacts of the global fashion industry."-- Cover page 4